Monitoring role of customer firms in suppliers and its effect on supplier value: Evidence from block acquisitions of suppliers by customer firms - Kang, Jun-Koo; Liu, Wei-Lin; Yi, Sangho; Zhang, Le (Journal of Financial Intermediation, 2015)
Using a large sample of block acquisitions, this paper examines the governance role of customers that acquire block ownership in supplier shares. We find that compared to targets acquired by noncustomers, those acquired by customers experience higher abnormal announcement returns, larger increases in post-acquisition long-term operating performance, and higher non-routine turnover of poorly performing CEOs. These results are evident when target managerial agency problems are highly detrimental to the supplier–customer relationship. The results support the view that customers’ nonfinancial claims in targets provide customers strong incentives to monitor target managers above and beyond previously documented monitoring by large shareholders.